Coupled Coincidence Point and Coupled Fixed Point Theorems for Weak Generalized Meir-Keeler Type Contractions in Ordered Partial Metric Spaces - Rao, K.P.R.; Rao, K.R.K. (Kathmandu University Journal of Science, Engineering and Technology, 2013)
In this paper we introduce weak generalized Meir-Keeler contractions and prove some coupled fixed point theorems for two mappings F: X x X ->X and g: X ->X on a partially ordered partial metric space. Our results generalize some recent results in the literature, for example, the results of Thabet Abdeljawad et.al [1] and Ali Erduran et.al [3]. Also, we give some illustrative examples.